Cornerstone at the confluence : navigating the Colorado River Compact's next century - Robison, Jason, 1975- (University of Arizona Press, 2022)
"Forty million people rely on the Colorado River system's flows. Commemorating the Colorado River Compact's 2022 centennial, this volume explores the past, present, and future of the "Law of the River" and its cornerstone, amid a twenty-two-year megadrought and ongoing negotiations over new water management rules that must be completed by 2026"--